2007
DOI: 10.1523/jneurosci.4104-07.2007
|View full text |Cite
|
Sign up to set email alerts
|

Focusing Effect of Acetylcholine on Neuroplasticity in the Human Motor Cortex

Abstract: Cholinergic neuromodulation is pivotal for arousal, attention, and cognitive processes. Loss or dysregulation of cholinergic inputs leads to cognitive impairments like those manifested in Alzheimer's disease. Such dysfunction can be at least partially restored by an increase of acetylcholine (ACh). In animal studies, ACh selectively facilitates long-term excitability changes induced by feed-forward afferent input. Consequently, it has been hypothesized that ACh enhances the signal-to-noise ratio of input proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
123
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(139 citation statements)
references
References 44 publications
10
123
1
5
Order By: Relevance
“…Fourth, interhemispheric inhibition must be accounted for, especially in motor cortex stimulation, where any motor effect on one side of the body will be followed by the opposite effect on the other side of the body (Vines et al, 2006). Fifth, when experimenting with patient groups, medication must be carefully considered, because it has been shown that different substances may significantly alter the effects of tDCS (Kuo et al, 2007;Kuo et al, 2008;Nitsche et al, 2003;Nitsche et al, 2004;Terney et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, interhemispheric inhibition must be accounted for, especially in motor cortex stimulation, where any motor effect on one side of the body will be followed by the opposite effect on the other side of the body (Vines et al, 2006). Fifth, when experimenting with patient groups, medication must be carefully considered, because it has been shown that different substances may significantly alter the effects of tDCS (Kuo et al, 2007;Kuo et al, 2008;Nitsche et al, 2003;Nitsche et al, 2004;Terney et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that immediate effects of tDCS are due to modulation of sodium and calcium channels, whereas lasting after effects of tDCS are due to N-methyl-Daspartate-receptor-dependent neuroplasticity (Nitsche et al, 2003). Similarly, rivastigmine, an acetylcholine agonist, is shown to block any tDCS induced excitatory or inhibitory effects on MEPs after 13-min=1-mA anodal or cathodal stimulation of the primary motor cortex (Kuo, Grosch, Fregni, Paulus, & Nitsche, 2007).…”
Section: Pharmacological Interactions With Tdcsmentioning
confidence: 96%
“…Pharmacological and magnetic resonance spectroscopy studies have established the role of tDCS in regulating different neurotransmitter systems including glutamate [26], GABA [27], dopamine [28], serotonin [29], and acetylcholine [30]. The neuroplastic after-effects of anodal and cathodal modulation have been linked to N-methyl-D-aspartate (NMDA) receptor-dependent plasticity [31•] and can be pharmacologically suppressed by the sodium channel blocker carbamazepine, the calcium channel blocker flunarizine [26], the NMDA receptor antagonist dextromethorphan (DMO) [32], and the β-blocker propranolol [33].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Recent studies have investigated the possibility of boosting PAS-and TDCSinduced plasticity using drugs, including those that act on cholinergic transmission (Kuo et al, 2007;Thirugnanasambandam et al, 2011;Grundey et al, 2012). Acetylcholine (ACh) may play an important role in attention, learning, and memory by modulating cortical LTP and LTD (Laviolette and van der Kooy, 2004;Changeux, 2010).…”
Section: Review Of Grundey Et Almentioning
confidence: 99%
“…Acetylcholine (ACh) may play an important role in attention, learning, and memory by modulating cortical LTP and LTD (Laviolette and van der Kooy, 2004;Changeux, 2010). After enhancing global cholinergic transmission with rivastigmine, a cholinesterase inhibitor, Kuo et al (2007) found that anodal TDCS failed to increase MEPs, whereas PAS 25 elicited long-term MEP enhancement. More recently, Thirugnanasambandam et al (2011) examined the specific contribution of the nicotinic ACh receptor (AChR) to PAS-and TDCSinduced plasticity in nonsmokers.…”
Section: Review Of Grundey Et Almentioning
confidence: 99%